Handmade electronic music: the art of hardware hacking - Collins, Nicolas 1954- (New York Routledge, 2009)
Handmade Electronic Music: The Art of Hardware Hacking provides a long-needed, practical, and engaging introduction to the craft of making - as well as creatively cannibalizing - electronic circuits for artistic purposes. With a sense of adventure and no prior knowledge, the reader can subvert the intentions designed into devices such as radios and toys to discover a new sonic world. At a time when computers dominate music production, this book offers a rare glimpse into the core technology of early live electronic music, as well as more recent developments at the hands of emerging artists. In addition to advice on hacking found electronics, the reader learns how to make contact microphones, pickups for electromagnetic fields, oscillators, distortion boxes, and unusual signal processors cheaply and quickly.This revised and expanded second edition is extensively illustrated and includes a DVD featuring eighty-seven video clips and twenty audio tracks by over one hundred hackers, benders, musicians, artists, and inventors from around the world, as well as thirteen video tutorials demonstrating projects in the book. Further enhancements include additional projects, photographs, diagrams, and illustrations.